2016
DOI: 10.1371/journal.pone.0158086
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Predictors of Socio-Emotional Development in a Sample of Egyptian Infants

Abstract: IntroductionEmotional problems are amongst the most critical concerns to be intentionally handled to enhance the wellbeing and development of children.ObjectiveTo determine the predictors of socio-emotional development of Egyptian infants related to infant feeding practices, aspects of infant and maternal health and socioeconomic status.Subjects and MethodsA cross-sectional comparative study included 322 breast fed, 240 bottle fed and 93 mixed fed infants, from 6–24 months of age, who were enrolled in the Well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 55 publications
(55 reference statements)
1
36
0
7
Order By: Relevance
“…Endpoints/constructs which were investigated in single studies only, i.e. fine and gross motor skills alone (Jonsdottir et al., ) and socio‐emotional skills (Metwally et al., ) were not considered further as they cannot be used to determine an appropriate age range of introduction of CFs.…”
Section: Assessment Of the Data On Infant And Child Development In Inmentioning
confidence: 99%
“…Endpoints/constructs which were investigated in single studies only, i.e. fine and gross motor skills alone (Jonsdottir et al., ) and socio‐emotional skills (Metwally et al., ) were not considered further as they cannot be used to determine an appropriate age range of introduction of CFs.…”
Section: Assessment Of the Data On Infant And Child Development In Inmentioning
confidence: 99%
“…The short‐term adverse health outcomes may include stunted growth (Lassi, Das, Zahid, Imdad, & Bhutta, ), increased risk of diarrhoeal diseases (Ogbo et al, ; Ogbo, Page, Idoko, Claudio, & Agho, ), micronutrient deficiencies, and increased risk of mortality (Ahmed, Prendiville, & Narayan, ; Black et al, ). In the long‐term, inappropriate complementary feeding can negatively affect cognitive development (Dewey & Adu‐Afarwuah, ; Woldehanna, Behrman, & Araya, ), work capacity (Martins et al, ), childbirth outcomes (Victora et al, ), and social–emotional interactions (Metwally et al, )…”
Section: Introductionmentioning
confidence: 99%
“…The short-term adverse health outcomes may include stunted growth (Lassi, Das, Zahid, Imdad, & Bhutta, 2013), increased risk of diarrhoeal diseases (Ogbo et al, 2017;Ogbo, Page, Idoko, Claudio, & Agho, 2016), micronutrient deficiencies, and increased risk of mortality (Ahmed, Prendiville, & Narayan, 2016;Black et al, 2013). In the long-term, inappropriate complementary feeding can negatively affect cognitive development (Dewey & Adu-Afarwuah, 2008;Woldehanna, Behrman, & Araya, 2017), work capacity (Martins et al, 2011), childbirth outcomes (Victora et al, 2008), and social-emotional interactions (Metwally et al, 2016) The World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) recommend the introduction of adequate, safe, and appropriate complementary foods for infants aged 6-8 months to meet nutritional and developmental needs (WHO, 2009;WHO & UNICEF, 2003). However, reports from low-and middleincome countries (LMICs) indicated that many infants and young children are not receiving appropriate complementary foods (Aguayo, 2017;Black et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies found that maternal anxiety and depression during pregnancy had a negative impact on the children's intelligence and personality development. The children grown up with their families with parental psychological abnormalities have a higher risk of social emotional behavior problems, even if parental psychological problems are within the subclinical range [6,29,30]. Meanwhile, parental education level, related to a variety of social family factors as parenting style, family atmosphere and economic condition, may have a greater impact on the children's emotional disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional sociality is the original form of socialization of infant, which will mature as individual psychology develops. Besides the in uence by infants' own factors (gender, age, whether they are only children, and personal temperament), the acquired family factors as the harmonious extent of parental marital relationship, the family's nancial status, the parental rearing styles, the educational level, and psychological and mental conditions are also play an important role that synergistically affects the development of infants' emotional sociality [6][7][8].…”
Section: Introductionmentioning
confidence: 99%